PELATIHAN PEMBAWA ACARA (PEWARA) BAGI PENGURUS OSIS SMP NEGERI 1 KALIREJO LAMPUNG TENGAH - Muntazir Muntazir (Bagimu Negeri, 2017)
Good master of ceremony understand some aspects (1) attitude and master of ceremony’s behavior, (2) the use of good language aspects, and (3) vocal technique. Then having ability to apply these aspects. Therefore, thraining for master of ceremony is required to be conducted in Junior High School 1 Kalirejo, Kalirejo Subdistrict,Central Lampung. Thus students especially OSIS member learn and apply these aspect in order that they have ability for being good master of ceremony. Keywords: Master of Ceremony, Attitude, Behavior, Language, Vocal